Poricoic acid A induces apoptosis and autophagy in ovarian cancer via modulating the mTOR/p70s6k signaling axis - Ma,Rui (2021)
Due to the high mortality and rapid disease progression, ovarian cancer remains one of the most common malignancies threatening the health of women. The present study was conducted to explore the anticancer effects and the underlying mechanisms of poricoic acid A (PAA), the main components of Poria cocos, on ovarian cancer. We investigated the anticancer effects of different concentrations of PAA in the SKOV3 cell line. Cell viability and proliferation were examined by CCK-8 assay. Cellular migration and invasion were assessed by the scratch and Transwell migration assays, respectively. The effect of PPA on cell apoptosis was measured by flow cytometry and caspase-3/8/9 colorimetric assay. Western blot was performed to detect protein level changes related to apoptosis and mTOR signaling pathways. The in vivo anticancer effect of PAA was evaluated using xenograft tumorigenesis model in nude mice. Our results showed that PAA suppressed SKOV3 cellular viability, migration, and invasion in a dosage-dependent manner. Flow cytometry results demonstrated PAA treatment could induce SKOV3 cell apoptosis. In addition, increased ratio of LC3-II/LC3-I (a marker for autophagosome formation) was observed after PAA treatment, as well as inhibition of m-TOR and p70s6k phosphorylation. In nude mice, PAA treatment reduced the xenograft tumor weight by 70% (P<0.05). In conclusion, our data suggested that PAA induced apoptosis and autophagy in ovarian cancer via modulating the mTOR/p70s6k signaling axis.